The Error Analysis of English Speech Sounds Perception Conducted by EFL Students: A Case Study of English Literature Students at STBA Technocrat - Bayu Andika Prasatyo; Dwi Nopiyadi; Devian Try Gustary (Universitas Cokroaminoto Palopo, 2022)
This study scrutinizes the phenomenon of misperception on adult EFL learners at STBA Technocrat. It aims to comprehend the sounds which are frequently misperceived as well as the types of misperception experienced by ten EFL learners in apprehending sound-alike words. This study is descriptive qualitative research that involves ten EFL learners majoring on English literature in semester six. The results show that EFL learners frequently misperceived vowels than consonants. Almost all of the participants experienced the three types of misperception, namely, deafness, mirage, and mutation, except for the one participant who did not experience mirage. The data show that there are several things that are able to influence participants’ perception. The first is the phonetics features of English speech sounds. According to the data, the writers discover that the participants experienced the misperception more towards sounds which have similarities on its phonetics features. The second is the phonological systems between English and Indonesian. The discoveries significantly show that the participants feel confused and are not familiar enough with the sounds that do not exist in their native language. The third is the inserted information. The more information is inserted, the less misperception will occur. The last is the participants’ grades of listening subjects (I-III). However, those grades could not be a benchmark of their ability of speech perception.